Consistency and Recovery in Retail Supply Chains. Issue 1 (15th February 2018) - Bendoly, Elliot; Craig, Nathan; DeHoratius, Nicole
Abstract : Practitioners and researchers describe inventory service level with metrics that communicate the likelihood of demand fulfillment without considering the ongoing capabilities of the supplier, for example, in‐stock and fill rate. We develop a method for measuring inventory service level that incorporates such supplier capabilities, namely consistency (the ability of a supplier to fulfill orders repeatedly) and recovery (the ability of a supplier to fulfill orders after a lapse in service). Using data from two retail supply chains, we illustrate our approach. To demonstrate the impact of consistency and recovery on supply chain performance, we model a retailer purchasing from competing suppliers with different levels of consistency and recovery. The model incorporates the retailer's uncertainty about demand and the retailer's uncertainty about its suppliers' service levels. We characterize how the retailer's orders and profitability change with a supplier's delivery performance through numerical experiments calibrated with field data. We find notable differences in market share across suppliers with similar traditional inventory service level metrics but differences in consistency and recovery. Further, we observe that a retailer can increase its profitability by determining orders via consistency and recovery in lieu of common metrics like in‐stock. Given the influence of consistency and recovery on supply chain outcomes, we discuss implications for practice and future research.